Particulate air pollution and the blood. Issue 11 (1st November 1999) - Seaton, Anthony; Soutar, Anne; Crawford, Vivienne; Elton, Robert; McNerlan, Susan; Cherrie, John; Watt, Monika; Agius, Raymond; Stout, Robert
Abstract : BACKGROUND: Particulate air pollution has been associated with excess deaths from, and increases in hospital admissions for, cardiovascular disease among older people. A study was undertaken to determine whether this may be a consequence of alterations in the blood, secondary to pulmonary inflammation caused by the action of fine particles on alveolar cells, by repeatedly measuring haematological factors in older people and relating them to measurements of exposure to airborne particles. METHODS: One hundred and twelve individuals aged 60+ years in two UK cities provided repeated blood samples over 18 months, 108 providing the maximum of 12 samples. Estimates of individual exposure to particles of less than 10 μm diameter (PM10 ), derived from a mathematical model based on activity diaries and comparative measurements of PM10 at multiple sites and during a variety of activities, were made for each three day period prior to blood sampling. The relationships between blood values and estimates of both personal exposure and city centre measurements of PM10 were investigated by analysis of covariance, adjusting for city, season, temperature, and repeated individual measurements. RESULTS: Estimated personal exposure to PM10 over the previous three days showed negative correlations with haemoglobin concentration, packed cell volume (PCV), and red blood cell count (p<0.001), and with platelets and factor VII levels (p<0.05). The changes in red cell indices persisted after adjustment for plasma albumin in a sample of 60 of the subjects. City centre PM10 measurements over three days also showed negative correlations with haemoglobin and red cell count (p<0.001) and with PCV and fibrinogen (p<0.05), the relationship with haemoglobin persisting after adjustment for albumin. C reactive protein levels showed a positive association with city centre measurements of PM10 (p<0.01). Based on a linear relationship, the estimated change in haemoglobin associated with an alteration in particle concentration of 100 μg/m 3 is estimated to have been 0.44 g/dl (95% CI 0.62 to 0.26) for personal PM10 and 0.73 g/dl (95% CI 1.11 to 0.36) for city centre PM10 measurements. CONCLUSIONS: This investigation is the first to estimate personal exposures to PM10 and to demonstrate associations between haematological indices and air pollution. The changes in haemoglobin adjusted for albumin suggest that inhalation of some component of PM10 may cause sequestration of red cells in the circulation. We propose that an action of such particles either on lung endothelial cells or on erythrocytes themselves may be responsible for changing red cell adhesiveness. Peripheral sequestration of red cells offers an explanation for the observed cardiovascular effects of particulate air pollution.